A national project : Syrian refugee resettlement in Canada - Hamilton, Leah K., 1980-; Veronis, Luisa, 1975-; Walton-Roberts, Margaret, 1968- (McGill-Queen's refugee and forced migration studies, 2020)
"Since the outbreak of the Syrian Civil War in 2011, over 5.6 million people have fled Syria and another 6.6 million remain internally displaced. By January 2017, a total of 40,081 Syrians had sought refuge across Canada in the largest resettlement event the country has experienced since the Indochina refugee crisis. Breaking new ground in an effort to understand and learn from the Syrian Refugee Resettlement Initiative that Canada launched in 2015, A National Project examines the experiences of refugees, receiving communities, and a range of stakeholders who were involved in their resettlement, including sponsors, service providers, and various local and municipal agencies. The contributors, who represent a wide spectrum of disciplines, include many of Canada's leading immigration scholars and others who worked directly with refugees. Considering the policy behind the program and the geographic and demographic factors affecting it, chapters document mobilization efforts, ethical concerns, integration challenges, and varying responses to resettling Syrian refugees from coast to coast. Articulating key lessons to be learned from Canada's program, this book provides promising strategies for future events of this kind. Showcasing innovative practices and initiatives, A National Project captures a diverse range of experiences surrounding Syrian refugee resettlement in Canada."--